Prevalence of Risk Factors for Diphtheria: CLTS and DPT-HB-HIB3 Immunization Coverage in East Java (Periode 2018-2020) - Niken Istania Nuryanti; Lucia Yovieta Hendrati (Universitas Airlangga, 2022)
Introduction: Diphtheria is an acute disease that is transmitted through air, saliva, and direct contact with patients. In the Community Lead Total Sanitation (CLTS) targets, air quality in the house is an indicator leading to diphtheria incidence as its bacteria can spread through the air. Efforts can be made to overcome diphtheria by providing DPT-HB-HiB3 immunization to increase body immunity and enforcing the CLTS program to improve air quality. Meanwhile, East Java experienced a decrease in CLTS and DPT-HB-HiB3 coverage in 2020. This study aimed to map the distribution of the disease and describe the correlation between diphtheria and its factors. Methods: This study evaluated diphtheria incidence in 38 regencies/cities in East Java. It used the Spearman correlation test to analyze secondary data from the Health Profile of East Java in 2018-2020. Data processing was done using Health Mapper and SPSS. Results and Discussion: No correlation was found between CLTS coverage and the incidence of diphtheria in 2018 (p = 0.207; OR = 0.201) while there was a correlation between DPT-HB-HiB3 immunization coverage and the incidence of diphtheria in 2018 (p = 0.006 ; OR = 0.441). Conclusion: CLTS coverage was not associated with the incidence of diphtheria in the province rather DPT-HB-HiB3 immunization coverage was. Education for public about the importance of DPT-HB-HiB3 immunization is required and maintaining a clean environment to prevent transmission of diphtheria.